Biomechanical comparison of straight DCP and helical plates for fixation of transverse and oblique bone fractures - Aksakal, Bunyamin; Gurger, Murat; Say, Yakup; Yilmaz, Erhan (Wroclaw Univ Technology, 2014)
Purpose: Biomechanical comparison of straight DCP and helical plates for fixation of transversal and oblique tibial bone fractures were analyzed and compared to each other by axial compression, bending and torsion tests. Method: An in vitro osteosynthesis of transverse (TF) and oblique bone fracture (OF) fixations have been analysed on fresh sheep tibias by using the DCP and helical compression plates (HP). Results: Statistically significant differences were found for both DCP and helical plate fixations under axial compression, bending and torsional loads. The strength of fixation systems was in favor of DC plating with exception of the TF-HP fixation group under compression loads and torsional moments. The transvers fracture (TF) stability was found to be higher than that found in oblique fracture (OF) fixed by helical plates (HP). However, under torsional testing, compared to conventional plating, the helical plate fixations provided a higher torsional resistance and strength. The maximum stiffness at axial compression loading and maximum torsional strength was achieved in torsional testing for the TF-HP fixations. Conclusion: From in vitro biomechanical analysis, fracture type and plate fixation system groups showed different responses under different loadings. Consequently, current biomechanical analyses may encourage the usage of helical HP fixations in near future during clinical practice for transverse bone fractures.
Keywords: straight DC plate; helical plate; biomechanics; fixation; bone fractures